THE REPRESENTATIONS OF TAIWAN'S FIRST FEMALE PRESIDENT IN THE MEDIA - Yasmine Anabel Pandjaitan (Universitas Sebelas Maret, 2019)
As the first female president in Taiwan, Tsai Ing-wen’s actions and words are crucial to the advancement of gender equality within the Chinese patriarchal society. Likewise, the media also have a role in shaping gender discourse which may or may not support the president’s attempt at empowering women in politics and other sectors of life. This paper examined the linguistic strategy used by President Tsai to represent herself as a strong female leader through her official statements and how the media represented her in their reports. The data were collected from local news reports and international news portals, and from her speeches as quoted by the media, starting from the year she was elected in 2016 to 2018. Using Fairclough’s Critical Discourse Analysis, it was apparent that President Tsai struggled with her role as a female leader in politics, with critics from persisting patriarchal society and pressure from emerging new values in Taiwan. The media, on the other hand, was divided in making representations for and against Tsai. The conclusion of this research is hoped to give a general description of gender and political dynamics under the new era of Tsai Ing-wen.